2018
DOI: 10.21608/jomes.2018.9463
|View full text |Cite
|
Sign up to set email alerts
|

Shifted Gegenbauer Operational Matrix and Its Applications for Solving Fractional Differential Equations

Abstract: This paper introduces a new numerical mechanism for solving multi-order fractional differential equations (MOFDEs) and systems of fractional differential equations, in which the fractional derivatives are expressed in Riemman-liouville (RL) sense. A new shifted ultraspherical (Gegenbauer) operational matrix (SGOM) of fractional integration of arbitrary order is induced. By using this matrix jointly with the Tau method, the solution of fractional differential equation (FDE) is decreased to the solution of a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The Gegenbauer polynomials C ( ) j (x), of degree j ∈ Z + , and associated with the parameter 𝛼 > −1 2 are a sequence of real polynomials in the finite domain [−1, 1]. They are a family of orthogonal polynomials which has many applications [32].…”
Section: Gegenbauer Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Gegenbauer polynomials C ( ) j (x), of degree j ∈ Z + , and associated with the parameter 𝛼 > −1 2 are a sequence of real polynomials in the finite domain [−1, 1]. They are a family of orthogonal polynomials which has many applications [32].…”
Section: Gegenbauer Polynomialsmentioning
confidence: 99%
“…• For = 1, the SFGPS reduced to the SGPs. Numerous studies have shown that the Gegenbauer polynomials (GPs) are very effective in solving a wide range of issues [32][33][34]. • The parameter 𝛼 > −0.5 distributes the Gegenbauer polynomials (GPs).…”
Section: Introductionmentioning
confidence: 99%
“…The approximation methods based on spectral techniques and orthogonal functions have become a rigorous tool for solving various fractional dynamical systems [36,37]. These nonlocal methods are efficient numerical schemes for discretising the nonlocal fractional differential operators [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of this research is to extract an accurate numerical method to solve the following models: Spectral techniques are one of the most effective and powerful numerical algorithms for solving differential and integral equations with integer and non-integer order derivatives. Spectral approaches such as pseudo spectral [4], Galerkin [5], and Tau [17] can be produced from a weighted residual method. The spectral collocation method is becoming more widely used, with applications in a variety of fields.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by exponential rates of convergence, great precision, ease of use, and effectiveness in handling a variety of problems. Besides the spectral methods, operational matrices are commonly utilized for solving these types of equations [17,5]. The current paper is based on the shifted fractional Gegenbauer polynomials for building the variable-order operational matrix of derivatives.…”
Section: Introductionmentioning
confidence: 99%